Na2Al2Ge3O10 center dot 2H(2)O: an aluminogermanate with the tetranatrolite topology - Tripathi, A; Johnson, GM; Kim, SJ; Parise, JB (ROYAL SOC CHEMISTRY, 2000)
An aluminogermanate, Na2Al2Ge3O10. 2H(2)O (NaAlGe-NAT), possessing the natrolite topology has been synthesized under hydrothermal conditions at 423 K from sodium- and tetramethylammonium-containing gels. Room temperature single crystal X-ray diffraction data indicate a tetragonal unit cell with a = 13.314(2) and c = 6.819(2) Angstrom, and space group I (4) over bar 2D. NaAlGe-NAT displays complete disorder of aluminium and germanium in the framework, with Ge/Al = 1.5. The substitution of germanium for silicon in the framework leads to a larger unit cell volume for NaAlGe-NAT compared with Na8Al8Si12O40. 8H(2)O (NaAlSi-NAT) and Na8Ga8Si12O40. 8H(2)O (NaGaSi-NAT) framework structures. The mean rotation angle Psi of the chains (composed of 4=1 secondary building units) relative to the a and b cell axes is 20.4 degrees, compared with 21.7 and 22.9 degrees calculated for NaGaSi-NAT and NaAlSi-NAT, respectively. Elliptical channels along the c-axis host well-ordered water molecules and sodium cations in fully occupied sites.
Keywords: CRYSTAL-STRUCTURE; COLLAPSIBLE FRAMEWORK; DISORDERED NATROLITE; NAT TOPOLOGY; FLEXIBILITY; DISTORTION; GERMANIUM